Tax Planning: Theory and Modeling - Saadia Kouroub; Lahcen Oubdi (Journal of Applied Business, Taxation and Economics Research, 2022)
The majority of taxpayers, whether individuals or corporations, seek to reduce their tax burden or to benefit from a certain tax saving. In this sense, taxpayers resort to various legal or even illegal tax planning practices. In this article, we seek to deepen the understanding of the concept of tax planning and to offer, to the various readers, new theoretical and empirical indicators to understand the motivations behind fiscally aggressive behavior. Indeed, after presenting the theoretical framework of the notion of tax planning, we will discuss the main theoretical and empirical sources that have attempted to model and estimate the extent of tax planning. At the end of our review of the theoretical and empirical literature, we can argue that the deterrence theory, which has dominated the earlier literature on tax planning, is insufficient to explain fiscally aggressive behavior, and that the modeling of tax planning practices depends to a large extent on the context of the estimated study and on the interpretations of tax laws.